Colombian Stock Market. Macroeconomic Determinants and the Role of the AFP - Uribe Gil, Jorge Mario; Mosquera López, Stephanía; Restrepo López, Natalia (Sociedad y Economía, 2013)
The Colombian stock market has grown considerably in recent decades, but it remainsilliquid and concentrated. This situation does not seem to be a consequence of the externalmacroeconomic fundamentals, neither to the internal ones, instead it responds tothe investment portfolios dynamics in charge of the AFP and to the Capital Account. Inthis article the recent evolution of the Colombian stock market is reviewed in comparativeterms, and several econometrics techniques, such as FMOLS, VAR and VEC models,are used in order to explain long-run relationships between macroeconomic variablesand the market development. It is found that macro-variables are relevant only since fewyears ago, and for the same period the role of AFP have been crucial.